Chemical profiling of cerebrospinal fluid by multiple reaction monitoring mass spectrometry12. Issue 18 (12th August 2016) - Ferreira, Christina R.; Yannell, Karen E.; Mollenhauer, Brit; Espy, Ryan D.; Cordeiro, Fernanda B.; Ouyang, Z.; Cooks, R. G.
Abstract : We report an accelerated biomarker discovery workflow and results of sample screening by mass spectrometry based on multiple reaction monitoring (MRM). Abstract : We report an accelerated biomarker discovery workflow and results of sample screening by mass spectrometry based on multiple reaction monitoring (MRM). This methodology shows promising initial results for the currently unsolved challenge of Parkinson's disease (PD) laboratory diagnosis by biomarker screening. Small molecules present in cerebrospinal fluid (CSF) at low parts per million levels are monitored using specific transitions connecting ion pairs. A set of such transitions constitutes a multidimensional chemical profile used to distinguish and characterize different CSF samples using multivariate statistical methods.